Lead Removal Process Modeling in Natural Zeólita Clinoptilolita through Dynamic and Batch Systems - Kleinübing, S. J.; C. da Silva, M. G. (Scientia Plena, 2011)
In this work, the uptake capacity of lead ions in clinoptilolite zeolite was investigated. The experiments were carried out in continuous system, at pH=5.0, with a flow rate of 25mL/min, an average particle size of 0.65mm and concentration of 300, 400, 600 and 700 ppm. A mathematical model was also applied to represent the dynamics of the column’s sorption. The equilibrium data were correlated using the Langmuir isotherm. The parameters necessary for this correlation were obtained using batch system. The results of the lead simulation converged very well with the experimental dynamic data. The mass transfer in the solid (K) was influenced by the initial metal concentration in the range studied.